BLUE GIANTS IN GALACTIC LONGITUDES 280 TO 330 - GONZALEZ, G; GONZALEZ, G (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1954)
A catalogue of 95 new OB stars classified between l=280° and 330° is presented. The data were obtained on objective prism plates, taken with the Tonantzintla Schmidt camera.
BOL OBS TONAN TACUB
Keywords: BLUE GIANTS, GALACTIC, LONGITUDES; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; GALAXIAS